2015
DOI: 10.1002/2015jd024095
|View full text |Cite
|
Sign up to set email alerts
|

CALIPSO‐inferred aerosol direct radiative effects: Bias estimates using ground‐based Raman lidars

Abstract: Observational constraints on the change in the radiative energy budget caused by the presence of aerosols, i.e., the aerosol direct radiative effect (DRE), have recently been made using observations from the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite (CALIPSO). CALIPSO observations have the potential to provide improved global estimates of aerosol DRE compared to passive sensor‐derived estimates due to CALIPSO's ability to perform vertically resolved aerosol retrievals over all surface types and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 86 publications
(95 reference statements)
2
44
0
Order By: Relevance
“…Figure 1b displays that the aerosol mostly occurs under 5 km m.s.l., and its extinction coefficient is exponentially weakened with the increase in altitude in South Asia. This result is consistent with previous work [42,43]. Moreover, the vertical aerosol extinction coefficient increases distinctly during the monsoon season in South Asia from 2006 to 2015, especially below 2 km.…”
Section: Of 17supporting
confidence: 93%
“…Figure 1b displays that the aerosol mostly occurs under 5 km m.s.l., and its extinction coefficient is exponentially weakened with the increase in altitude in South Asia. This result is consistent with previous work [42,43]. Moreover, the vertical aerosol extinction coefficient increases distinctly during the monsoon season in South Asia from 2006 to 2015, especially below 2 km.…”
Section: Of 17supporting
confidence: 93%
“…Level 2 atmospheric samples classified as "clear-air" (i.e., no feature is detected) are assumed in the level 3 algorithm to have aerosol extinction equal to 0 km Several researchers have recently sought to characterize the optical depths of the aerosol layers undetected by CALIOP using collocated observations (Kacenelenbogen et al, 2011;Sheridan et al, 2012;Rogers et al, 2014;Thorsen and Fu, 2015;Toth et al, 2018) or independent retrievals Kim et al, 2017). Exactly how these undetected layers affect the level 3 mean extinction is difficult to estimate given that the resulting underestimate depends on the 20 magnitude of missing extinction and the frequency of non-detection.…”
Section: Aerosol In "Clear-air" Regionsmentioning
confidence: 99%
“…[] found that the marine boundary aerosols below the elevated smoke layers are frequently undetected by the CALIOP layer detection algorithm due to attenuation, which leads to underestimation of CALIOP AOD for smoke aerosols. Thorsen and Fu [] also showed that CALIOP detects significantly less aerosol layers for the middle and lower atmosphere compared to ground‐based Raman lidars at two Atmospheric Radiation Measurement sites. Moreover, they noted that the undetected aerosols lead to underestimation of the CALIOP‐inferred aerosol direct radiative effect by 30–50%.…”
Section: Introductionmentioning
confidence: 99%